Comparative Analysis of Defense Responses in Chocolate Spot-Resistant and -Susceptible Faba Bean (Vicia faba) Cultivars Following Infection by the Necrotrophic Fungus Botrytis fabae - Mahmoud H. El-Komy (The Plant Pathology Journal, 2014)
In this study, resistance responses were investigated during the interaction of Botrytis fabae with two faba bean cultivars expressing different levels of resistance against this pathogen, Nubaria (resistant) and Giza 40 (susceptible). Disease severity was assessed on leaves using a rating scale from 1 to 9. Accumulation levels of reactive oxygen species (ROS), lipid peroxidation and antioxidant enzymes (superoxide dismutase, catalase and ascorbate peroxidase) were measured in leaf tissues at different times of infection. The expression profiles of two pathogenesis-related proteins (PRPs) encoded by the genes PR-1 and β-1,3-glucanase were also investigated using reverse transcription RT-PCR analysis. The accumulation of these defense responses was induced significantly in both cultivars upon infection with B. fabae compared with un-inoculated controls. The resistant cultivar showed weaker necrotic symptom expression, less ROS accumulation, a lower rate of lipid peroxidation and higher activity of the enzymatic ROS scavenging system compared with susceptible cultivar. Interestingly, ROS accumulated rapidly in the resistant leaf tissues and peaked during the early stages of infection, whereas accumulation was stronger and more intense in the susceptible tissues in later stages. Moreover, the response of the resistant cultivar to infection was earlier and stronger, exhibiting high transcript accumulation of the PR genes. These results indicated that the induction of oxidant/antioxidant responses and the accumulation of PRPs are part of the faba bean defense mechanism against the necrotrophic fungus B. fabae with a different intensity and timing of induction, depending on the resistance levels.